2017
DOI: 10.1016/j.cell.2017.04.033
|View full text |Cite
|
Sign up to set email alerts
|

An Atomic Structure of the Human Spliceosome

Abstract: Mechanistic understanding of pre-mRNA splicing requires detailed structural information on various states of the spliceosome. Here we report the cryo electron microscopy (cryo-EM) structure of the human spliceosome just before exon ligation (the C complex) at an average resolution of 3.76 Å. The splicing factor Prp17 stabilizes the active site conformation. The step II factor Slu7 adopts an extended conformation, binds Prp8 and Cwc22, and is poised for selection of the 3'-splice site. Remarkably, the intron la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
282
1
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 241 publications
(313 citation statements)
references
References 78 publications
9
282
1
6
Order By: Relevance
“…While haploinsufficiency of EIF4A3, RBM8A, and MAGOH lead to premature neuronal differentiation and apoptosis in the mutant brains (Mao et al, 2016; McMahon et al, 2016), similar reduction in CASC3 levels (or even its near complete depletion) does not cause the same defects but leads to a more general developmental delay (Mao et al, 2017). We note that a view contrary to our findings is presented by the recently reported human spliceosome C* structure, where CASC3 is seen bound to the trimeric EJC core (Zhang et al., 2017). As the spliceosomes described in these structural studies were assembled in vitro in nuclear extracts, it is possible that CASC3 present in extracts can enter pre-assembled spliceosomes and interact with EJC.…”
Section: Discussioncontrasting
confidence: 99%
“…While haploinsufficiency of EIF4A3, RBM8A, and MAGOH lead to premature neuronal differentiation and apoptosis in the mutant brains (Mao et al, 2016; McMahon et al, 2016), similar reduction in CASC3 levels (or even its near complete depletion) does not cause the same defects but leads to a more general developmental delay (Mao et al, 2017). We note that a view contrary to our findings is presented by the recently reported human spliceosome C* structure, where CASC3 is seen bound to the trimeric EJC core (Zhang et al., 2017). As the spliceosomes described in these structural studies were assembled in vitro in nuclear extracts, it is possible that CASC3 present in extracts can enter pre-assembled spliceosomes and interact with EJC.…”
Section: Discussioncontrasting
confidence: 99%
“…The coordinates files of SET/TAF‐Iβ and NRP1 were obtained using homology models based on PDB ID 2E50 , as described previously . The following protein structures were constructed as homology models with SWISS‐MODEL: STRAP (based on 3JAP ), eiF2γ (based on 6FEC, ), BiP1 (based on 6HAB, ), RD21 (based on 5EGW, ), TCL (based on 6ES4, ), and Sm/D1 (based on 5XJC, ).…”
Section: Cytochrome C In the Cytoplasm: Established And New Targetsmentioning
confidence: 99%
“…Proteomics studies show that SF3b proteins are depleted by 70% in the C complex relative to the B act complex (Agafonov et al 2011). Moreover, the cryo-EM structure of the human C * complex revealed that the SF3b proteins were absent (Zhang et al 2017), pointing to their departure. These data are all consistent with the paradigm that SF3B1 splicing modulators act early in spliceosome assembly by weakening interactions between the U2 snRNP and the pre-mRNA, likely impeding the formation of the "A complex" (Roybal and Jurica 2010;Corrionero et al 2011;Folco et al 2011;Effenberger et al 2014;Vigevani et al 2017).…”
Section: Compound-binding Mode and Sarmentioning
confidence: 99%